MARKETING MIX SEBAGAI ALAT PEMBEDA DALAM PERSAINGAN - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2012)
Marketers must not only formulate the broad strategies to achieve its marketing objectives but also plan marketing mix programs. Many good strategies fail when it comes to development of specific marketing - mix tactics. Decision must be made to transform marketing strategy to marketing mix and to provide competitive advantageous in the competitive market place and in the same time to provide what market needs.Key words : Integrated Marketing, Marketing Mix, Differentiation, Customer Value, Product, Place, Marketing Channel, dan Promotion.